THE EFFECT OF PROWRITINGAID AS ARTIFICIAL INTELLIGENCE (AI) ON STUDENT'S ENGAGEMENT - Arcelina Putri Adelia; Tatik Irawati (LPPM Universitas PGRI Jombang, 2025)
Technology has developed rapidly and people need to adapt to this development. One of them is a technology called artificial intelligence. In the education field, the utilization of artificial intelligence is needed for students. Therefore, this current study aimed to determine whether using ProWritingAid as artificial intelligence affects student engagement. This current study was conducted as pre-experimental research with one group pretest-posttest design. The second-semester English language education students were selected by the researchers as the sample through the total sampling method. Data was gathered through pre-questionnaires as well as post-questionnaires. The questionnaire results were used to score student’s engagement. Based on the result finding, The mean score pre-questionnaire was 56.62 and post-questionnaire was 62.62. Moreover, the result data analysis on the Wilcoxon-Signed Rank Test revealed the sig (2-tailed) of 0.000 < 0.05. Simply, the null hypothesis (Ho) is rejected, whereas the alternative hypothesis (Ha) is accepted. Thus, a conclusion can be made that the application of ProWritingAid positively and significantly affects student engagement. Additionally, further researchers can investigate the use of ProWritingAid with other artificial intelligence tools so that can be seen as the most effective application to be used